Robust fault tolerant control based on sliding mode method for uncertain linear systems with quantization - Hao, Li-Ying; Yang, Guang-Hong (ISA transactions, 2013)
This paper is concerned with the problem of robust fault-tolerant compensation control problem for uncertain linear systems subject to both state and input signal quantization. By incorporating novel matrix full-rank factorization technique with sliding surface design successfully, the total failure of certain actuators can be coped with, under a special actuator redundancy assumption. In order to compensate for quantization errors, an adjustment range of quantization sensitivity for a dynamic uniform quantizer is given through the flexible choices of design parameters. Comparing with the existing results, the derived inequality condition leads to the fault tolerance ability stronger and much wider scope of applicability. With a static adjustment policy of quantization sensitivity, an adaptive sliding mode controller is then designed to maintain the sliding mode, where the gain of the nonlinear unit vector term is updated automatically to compensate for the effects of actuator faults, quantization errors, exogenous disturbances and parameter uncertainties without the need for a fault detection and isolation (FDI) mechanism. Finally, the effectiveness of the proposed design method is illustrated via a model of a rocket fairing structural-acoustic. •A sliding mode fault tolerant controller is proposed for uncertain linear systems.•It is assumed that control input and state signals are quantized before transmission.•Matrix full-rank factorization technique is incorporated with sliding surface design.•An adjustment range of quantization sensitivity for fault tolerant control systems is given.•The proposed scheme does not require any fault detection and diagnosis mechanism.